2015
DOI: 10.1007/s00421-015-3284-8
|View full text |Cite
|
Sign up to set email alerts
|

Does a 20-week aerobic exercise training programme increase our capabilities to buffer real-life stressors? A randomized, controlled trial using ambulatory assessment

Abstract: Using a randomized controlled trial and a real-life stressor, we could show that exercise appears to be a useful preventive strategy to buffer the effects of stress on the autonomic nervous system, which might result into detrimental health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 70 publications
6
68
1
1
Order By: Relevance
“…It seems clear that aerobic exercise of light and moderate intensity prevents stress (Haaren et al, 2016), and this agrees with Hannus (2012) who stated that the motives for energy release and fun had an inverse relationship with exercise dependence. However, what type of exercise would have to be researched, because if subjects who engage in physical activity by releasing energy do so at high intensities and high exercise frequencies, they may be at increased risk of exercise dependence, as seen in other populations (Phelan et al, 2011;Shin and You, 2015) where those who perform a greater amount and intensity of exercise have greater exercise dependence.…”
Section: Dicussionsupporting
confidence: 78%
“…It seems clear that aerobic exercise of light and moderate intensity prevents stress (Haaren et al, 2016), and this agrees with Hannus (2012) who stated that the motives for energy release and fun had an inverse relationship with exercise dependence. However, what type of exercise would have to be researched, because if subjects who engage in physical activity by releasing energy do so at high intensities and high exercise frequencies, they may be at increased risk of exercise dependence, as seen in other populations (Phelan et al, 2011;Shin and You, 2015) where those who perform a greater amount and intensity of exercise have greater exercise dependence.…”
Section: Dicussionsupporting
confidence: 78%
“…Randomized controlled trials studies showed that exercise is an effective method for improving stress symptoms and quality of life also among students. For instance, a 20-week aerobic exercise training reduced psychological stress and physiological stress responses during the academic examination period (end of the semester) in sedentary students (von Haaren et al, 2016). In addition, ex ercise intervention significantly reduced study-related fatigue (emotional exhaustion, overall fatigue, and need for recovery), which is known as an outcome of prolonged study stress (de Vries, van Hooff, Geurts, & Kompier, 2016).…”
Section: Findings: Exerc Ise Interventions As a Strategy For Coping Wmentioning
confidence: 99%
“…There are even other evidences that show aerobic exercises can cause a positive change in the density of neural conveyer in neural system and could have anti stress effects on reducing muscular tension and hormones level [28][29][30]. In another study, von Haeren et al (2016) reported that through affecting automatic neural system, aerobic exercises can reduce the level of stress and anxiety, which endanger the human health, and take a positive step toward reducing anxiety and depression [31].This may happen due to changes in cortisol level during doing aerobic exercises because various studies have reported the impact of aerobic exercise on reducing the level of cortisol and anxiety [32,33].…”
Section: Discussionmentioning
confidence: 99%